2022
DOI: 10.1002/cam4.4975
|View full text |Cite
|
Sign up to set email alerts
|

Five EMT‐related genes signature predicts overall survival and immune environment in microsatellite instability‐high gastric cancer

Abstract: Background Microsatellite instability‐high (MSI‐H) subgroup of gastric cancer (GC) is characterized by a high tumor mutational burden, increased lymphocytic infiltration, and enhanced inflammatory cytokines. GC patients with MSI‐H status have a good response to immune checkpoint blockade management. However, heterogeneity within the subtype and the underlying mechanisms of shaping tumor microenvironments remain poorly understood. Methods RNA expression levels and clinical parameters of GC were obtained from Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“… 23 , 24 Therefore, in-depth exploration of the invasion and metastasis mechanism of gastric cancer and identification of key molecules in it have important potential application value in gastric cancer research. 25 , 26 , 27 As a key regulatory factor of cancer, lncRNAs regulate the expression of cancer-related genes at different levels. Convincing evidence indicates that lncRNAs play an important role in the pathogenesis of GC and have great value for GC diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 Therefore, in-depth exploration of the invasion and metastasis mechanism of gastric cancer and identification of key molecules in it have important potential application value in gastric cancer research. 25 , 26 , 27 As a key regulatory factor of cancer, lncRNAs regulate the expression of cancer-related genes at different levels. Convincing evidence indicates that lncRNAs play an important role in the pathogenesis of GC and have great value for GC diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown the involvement of BMP1 in gastric and non-small cell lung cancer metastases [ 39 ]. Furthermore, PCOLCE plays a key role in promoting lung metastasis of osteosarcoma [ 40 ] and participates in EMT [ 41 ]. A recent study has shown that PCOLCE2 stimulates the production of reactive oxygen species in neutrophils [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Procollagen C-endopeptidase enhancer 2 (PCOLCE2) refers to a collagen-binding protein that binds to the C-terminal pro-peptide of types I and II procollagens and could enhance the cleavage of the pro-peptide by BMP1 ( 42 ). PCOLCE2 can be considered as an EMT-linked gene for anticipating the prognosis of gastric cancer patients ( 43 , 44 ) and the metastasis ability of COAD ( 45 ). However, none of the studies determined the role of PCOLCE2 in anoikis.…”
Section: Discussionmentioning
confidence: 99%